2019
DOI: 10.1073/pnas.1821399116
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of ER–plasma membrane contact sites but not STIM1 phosphorylation inhibits Ca 2+ influx in mitosis

Abstract: Store-operated Ca2+ entry (SOCE), mediated by the endoplasmic reticulum (ER) Ca2+ sensor stromal interaction molecule 1 (STIM1) and the plasma membrane (PM) channel Orai1, is inhibited during mitosis. STIM1 phosphorylation has been suggested to mediate this inhibition, but it is unclear whether additional pathways are involved. Here, we demonstrate using various approaches, including a nonphosphorylatable STIM1 knock-in mouse, that STIM1 phosphorylation is not required for SOCE inhibition in mitosis. Rather, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 78 publications
3
29
0
Order By: Relevance
“…Progression through the cell cycle is controlled by regulated degradation of cyclins, but local Ca 2+ signals are also important at critical stages ( Keith et al., 1985 ; Parry et al., 2005 ; Zhao et al., 2019 ), including nuclear envelope breakdown, the transition from metaphase to anaphase and cytokinesis. The mechanisms are largely unresolved, but because store-operated Ca 2+ entry is inhibited during meiosis and mitosis ( Smyth and Putney, 2012 ; Yu et al., 2019 ), the Ca 2+ signals are probably evoked by IP 3 Rs. We have shown that cells can proliferate without IP 3 Rs ( Figure S1 A) ( Alzayady et al., 2016 ; Ando et al., 2018 ; Atakpa et al., 2019 ; Sugawara et al., 1997 ), but their behavior is compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progression through the cell cycle is controlled by regulated degradation of cyclins, but local Ca 2+ signals are also important at critical stages ( Keith et al., 1985 ; Parry et al., 2005 ; Zhao et al., 2019 ), including nuclear envelope breakdown, the transition from metaphase to anaphase and cytokinesis. The mechanisms are largely unresolved, but because store-operated Ca 2+ entry is inhibited during meiosis and mitosis ( Smyth and Putney, 2012 ; Yu et al., 2019 ), the Ca 2+ signals are probably evoked by IP 3 Rs. We have shown that cells can proliferate without IP 3 Rs ( Figure S1 A) ( Alzayady et al., 2016 ; Ando et al., 2018 ; Atakpa et al., 2019 ; Sugawara et al., 1997 ), but their behavior is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ signals typically arise from a combination of Ca 2+ release from intracellular stores, predominantly within the endoplasmic reticulum (ER), and Ca 2+ entry across the plasma membrane. Store-operated Ca 2+ entry, where loss of Ca 2+ from the ER triggers opening of Ca 2+ channels in the plasma membrane, is the most widely expressed Ca 2+ entry pathway, but it is completely inhibited during mitosis ( Smyth et al., 2009 ; Yu et al., 2019 ). Hence, mitotic Ca 2+ signals are likely to be due entirely to release of Ca 2+ from intracellular stores ( Ciapa et al., 1994 ), most likely mediated by opening of inositol 1,4,5-trisphosphate receptors (IP 3 Rs), which are ubiquitously expressed intracellular Ca 2+ channels ( Rossi and Taylor, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Orai1 internalization appears to be specific to oocyte meiosis 9 , 10 , 33 and is not observed during mitosis 34 . Furthermore, during interphase Orai1 recycles continuously with rapid kinetics at the PM and its membrane residence is modulated by Ca 2+ store content as well interaction with the CCT chaperonin complex 7 , 8 .…”
Section: Discussionmentioning
confidence: 91%
“…Considering its role as a major organizing compartment, it is likely that the inheritance of the ER is regulated by yet unknown control mechanisms. Recently, it has been shown that the ER–PM CSs undergo significant changes in morphology and function during mitosis (Yu et al, 2019). One of the major functions of CSs is to control Ca 2+ signaling through the store-operated Ca 2+ entry (SOCE), which depends on the integrity of ER–PM CS to allow contact between the proteins STIM1 and Orai1 (Yu et al, 2019).…”
Section: Structural Reorganization Of Other Organelles During Mitosismentioning
confidence: 99%
“…Therefore, the down-regulation of ER–PM junctions in mitosis induces SOCE inhibition by preventing the interaction of STIM1 with Orai1. This inhibition could affect not only Ca 2+ signaling but also lipid metabolism and membrane structure (Yu et al, 2019).…”
Section: Structural Reorganization Of Other Organelles During Mitosismentioning
confidence: 99%